RODUCTION IMPROVEMENT AND PRODUCT MARKET EXPANSION OF TEYENG BATIK AND TULIP BATIK OF KANDANGAN VILLAGE,BENOWO DISTRICT, SURABAYA - Sri Andayani; Endang Indartuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Batik clothing was originally only worn on Swadesi days or on Friday. Becauseof its comfort and beauty, it had almost become daily clothing, either for workor during leisure. In Kandangan Benowo village of Surabaya, there wereseveral groups of Batik makers who had various style and materials, includingmaterials for batik stain of rust known as Teyeng batik and Tulip batik ofSurabaya. The problem that batik crafters as Mr. Firman and Ibu Siti Aminahwere facing was that there was not enough market demand for Teyeng batik andTulip batik because of too long process it took for batik Teyeng and Tulip forBatik to gain the optimal results. Besides, its price was relatively expensive. Tosolve the problem they intend to broaden their products not only handmadebatik but also printing batik and semi printing batik. However, they have nothad the equipment, were lack of funding to buy the equipment, and were lack ofmanagement knowledge to run the business. Therefore, there was a need oftechnological engineering, training, and mentoring about the businessmanagement. Some solutions had been undertaken and agreed, such asproviding effective technology consisting: batik designed table of glass, printedbearing table, wok, canting, training skills to use the equipment, andtraining/mentoring on business management, simple bookkeeping, training onmarketing techniques and strategies, and providing brochures and banners. Theoutputs were: 1). The availability of 2 glass tables of 115 cm x 75 cm size andof 75 cm height made of aluminum for 2 partners; 2) the availability of 2 batikprinting desks of 90x90x 7 cm size, filled with water, sponge, carpet, paper andplastic glass cement; 3) the existing of 2wax woks of 45 cm diameter made ofiron or copper and containing copper strands; 4) the availability of sealedcanting made of copper, of 30 x 30 cm size and 2 procurement brochures as amarketing medium ; 5) the increasing capacity of business management andmarketing strategy; 6) the scientific paper for journal on community service.The implementation method were training and mentoring methods, learning bydoing, and participatory methods. The results were that SME partners wereable to operate the introduced equipment, the2 times of the increasing products;the occurrence of market expansion with their batik printing equipment, and inAugust 2016 the SME partners have received orders on 500 batik shawls fromthe House Of Sampoerna for a 2 week-delivery order to be sent to the Swissembassy.Keywords: Teyeng (iron rust), participatory methods (learning by doing)